Teaching Indonesian Using the Think, Pair, and Share Model as a Strategy to Improve Oral Expression Skills - Ni Made Sumariyanti; Pelipus Ngongo Bulu; Ni Nyoman Satriani; Angel Veranita Sari Tupen; I Nyoman Sudiana; Ida Bagus Putra Yasa (International Journal of Language and Literature, 2025)
The problem faced in the Indonesian language learning process so far is students' lack of courage and skills in expressing opinions orally in class, which is caused by a learning approach that is still teacher-centered and does not provide enough space for students to think critically and speak. Therefore, this study aims to improve fifth-grade elementary school students' oral expression skills through the implementation of the Think, Pair, and Share (TPS) learning model. This study uses a quantitative approach, employing the One-Shot Case Study method with one group of fifth-grade students as research subjects. The learning process is carried out through three main stages in the TPS model: independent thinking, pair discussion, and open sharing of results with the class. The instruments used are observation sheets and speaking-skills performance tests, with indicators including fluency in speaking, clarity of opinion content, courage, appropriate use of language, and the ability to listen to friends' responses. The study showed a significant increase across all indicators of speaking skills after the implementation of the TPS model. This proves that the TPS model is not only able to improve learning outcomes but also to build students' confidence in speaking and increase positive interactions among students. Thus, this learning model can serve as a strategic alternative for Indonesian language learning to improve students' oral communication competencies.